Muḥammad the Prophet and Arabia - Rubin, Uri 1944- (Variorum collected studies series)
Comprises articles dealing with qur'anic and post-qur'anic aspects of the Prophet Muhammad's image and religious environment. This title analyses Muhammad's prophecy as reflected in the Qur'an and the post-qur'anic sources of sira (Muhammad's biography), tafsir (Qur'an exegesis), ta'rikh (historiography) and hadith (Muslim tradition)